2018
DOI: 10.13005/bbra/2618
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of G2350A Polymorphism of the Angiotensin-Converting Enzyme (ACE) Gene in Chronic Kidney Disease

Abstract: Chronic kidney disease (CKD) becomes a major problem for world health. Numerous studies have documented that the polymorphisms in angiotensin-converting enzyme (ACE) gene may contribute to an individual risk for the loss of kidney function. The present study was undertaken to evaluate the possible relationship between ACE G2350A gene polymorphism and the risk of CKD in Uttar Pradesh population. A total of 379 (159 CKD patients and 220 healthy controls) subjects were recruited for this study. All subjects were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Also, in ACE I/D polymorphism, the carriers of the I allele and A allele of ACE G2350A were more frequent in the diabetic patients than the control group. Furthermore, Verma et al 25 reported that patients with AA genotype were at lower risk for CKD in comparison with those with GG genotype. In current study, A-allele exhibited lower significant frequency in diabetic cases.…”
Section: Discussionmentioning
confidence: 99%
“…Also, in ACE I/D polymorphism, the carriers of the I allele and A allele of ACE G2350A were more frequent in the diabetic patients than the control group. Furthermore, Verma et al 25 reported that patients with AA genotype were at lower risk for CKD in comparison with those with GG genotype. In current study, A-allele exhibited lower significant frequency in diabetic cases.…”
Section: Discussionmentioning
confidence: 99%